Competitive Intelligence: A Necessity for Qualitative Library Service Delivery in 21st Century Academic Libraries in Nigeria - Makinde, Omawumi O.; Ogungbo, Wakil O. (MiddleBelt Journal of Library and Information Science, 2015)
The paper looks at the importance and duties of libraries generally and that of academic libraries specifically. It goes on to do an exposition on Nigerian academic libraries and it discovers that Nigerian academic libraries are faced with challenges. The concept of information needs and academic libraries services in the 21st century is also considered and it is concluded that if Nigerian academic libraries are to function effectively, there is the need to infuse business intelligence into the information business in Nigerian academic institution then will the academic libraries have what it takes to meet the information needs of Nigerians that go through these institutions in the 21st century for their individual and national development.